Preliminary Phytochemical Investigation and Screening of Antimicrobial Activity of Leaf Extracts of Artocarpus altilis - Raman, Vasugi; Sudhahar, D.; Anandarajagopal, K. (Asian Journal of Biological and Life Sciences, 2012)
Plants and animals are main source for the medicines, where active compounds were derived from these sources and formulated as drugs according to the current needs to treat various human ailments.In this present study, petroleum ether, chloroform, methanol, ethanol and aqueous extracts of Artocarpus altilis were prepared using cold maceration technique. All the extracts were screened for its antibacterial and antifungal activities by disc diffusion method. The extracts tested exhibited moderate to good activity against the selected bacteria and fungi when compared with standard drug, amoxicillin and fluconazole respectively. The methanol extract showed highest zone of inhibition in diameter (mm) than aqueous extract followed by ethanol extract against most of the pathogens. The phytochemical tests revealed that the presence of flavonoids, and tannins which might be responsible for the antimicrobial activity of the extracts. The study concluded that A. altilis could be a new potential source of antibiotics that could be beneficial for infectious diseases.